Chromium Removal from Tannery Wastewater via a Hydroponic Technique with Vetiver Grass (Vetiveria zizanioides) - Ismot Zereen; Md. Zainul Abedin; Md. Siddikur Rahman; Debasish Pandit (Applied Environmental Research)
This research aimed to investigate the effects of hydroponically cultivated vetiver grass (Vetiveria zizanioides) on the treatment of tannery wastewater for chromium (Cr) removal in Bangladesh. The field experiment involved 9 containers, which were separated into 3 groups: tannery wastewater with hydroponically planted vetiver, tannery wastewater without vetiver (control), and a group with vetiver grown in tap water. The tap water group was used solely for plant growth assessment, whereas only the control and hydroponic vetiver groups were evaluated for Cr and water quality parameters. Throughout the 45-day trial period, Cr and other water quality parameters were analyzed at 15-day intervals. The findings showed that the floating platform method of cultivating vetiver grass was significantly effective (p<0.05) in eliminating pollutants. The observed reduction rate for pH was 15.19%, whereas the treatment efficiencies for electrical conduc-tivity, biological oxygen demand, chemical oxygen demand, turbidity, total suspended solids, total dissolved solids, and Cr were 35.42%, 84.66%, 81.21%, 33.17%, 83.28%, 72.55%, and 79.71%, respectively. With respect to plant growth, vetiver grass is well established and thrives in tannery wastewater, achieving a root length of 22.5 cm after 45 days. Most contaminants significantly decreased (p<0.05) after treatment and were below the maximum permissible discharge limits, with only a few parameters remaining above the standards. The results provide evidence to support extensive research and application of the vetiver hydroponic technique as a cost-effective wastewater treatment method in Bangladesh.